The Influence Of Customer Experience And Perceived Value On Brand Loyalty Through Customer Satisfaction A Case Study Of Mie Gacoan - Wella Desintan Widika; Zaenul Mutaqien; Edwin Agus Buniarto (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to examine the effect of customer experience and perceived value on brand loyalty through customer satisfaction among Mie Gacoan consumers in Kediri City. A quantitative survey method was employed involving 170 respondents who had purchased Mie Gacoan products at least three times. Data were collected through an online questionnaire using a five-point Likert scale and analyzed with Partial Least Squares–Structural Equation Modeling (PLS-SEM) using SmartPLS 3.0. The findings reveal that perceived value has a positive and significant effect on customer satisfaction and brand loyalty. Customer satisfaction also significantly influences brand loyalty and mediates the relationship between perceived value and brand loyalty. In contrast, customer experience does not significantly affect customer satisfaction or brand loyalty, either directly or indirectly. These results imply that strengthening perceived value through product quality, price fairness, and service consistency is more important in fostering satisfaction and sustaining brand loyalty at Mie Gacoan Kediri.